Relationship Between Hope and Quality of Life in Patients with Advanced Cancer in Uruguay: An Observational Analysis (Global Journal of Medical Research, 2023)
Introduction International research suggests a beneficial effect of hope on quality of life in advanced-stage cancer patients Specific evidence for Latin America and Uruguay is limited highlighting the need to explore this relationship for regional clinical strategies Objective To evaluate the correlation between hope and quality of life in Uruguayan patients with advanced cancer Materials and Methods This observational analytical-descriptive and cross-sectional study used the Herth Hope Index HHI and the Functional Assessment of Cancer Therapy - General FACTG Quality of Life questionnaire It included 59 patients aged 18 or older diagnosed with advanced non-curable cancer
Keywords: cancer; palliative care; hope; quality of life; FACT-G; herth index